The Productivity Impact of Global Warming: Firm-Level Evidence for Europe - Nicola Gagliardi; Elena Grinza; François Rycx (Global Labor Organization (GLO), 2024)
In this paper, we investigate the impact of rising temperatures on firm productivity using longitudinal firm-level balance-sheet data from private sector firms in 14 European countries, combined with detailed weather data, including temperature. We begin by estimating firms' total factor productivity (TFP) using control-function techniques. We then apply multiple-way fixed-effects regressions to assess how higher temperature anomalies affect firm productivity - measured via TFP, labor productivity, and capital productivity. Our findings reveal that global warming significantly and negatively impacts firms' TFP, with the most adverse effects occurring at higher anomaly levels. Labor productivity declines markedly as temperatures rise, while capital productivity remains unaffected - indicating that TFP is primarily affected through the labor input channel. Our moderating analyses show that firms involved in outdoor activities, such as agriculture and construction, are more adversely impacted by increased warming. Manufacturing, capital-intensive, and blue-collar-intensive firms, compatible with assembly-line production settings, also experience significant productivity declines. Geographically, the negative impact is most pronounced in temperate and mediterranean climate areas, calling for widespread adaptation solutions to climate change across Europe.
Keywords: D24; J24; Q54; 330; Climate change; Global warming; Firm productivity; Total factor productivity (TFP); Semiparametric methods to estimate production functions; Longitudinal firm-level data